(3TQM bUjOI YHO GdYRjR Hf JeGes - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdCMO GdUeO GdPi dGJgJOi GdbdhH dcfg YXeJg hHYO aEf GdeGVjf ef Phi GdYdhe GdadSajI hbO bQCJ cKjQkG ef cdGe GdChGFd ahLOJe eJabjf ai LejY GdcJH s
(3BNQgG (B:s
(3bGd NGdO Hf jRjO Cf GdWHGFY SHYI ef SHYI Je TQM gPg GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdcjejGA h GdWHjYjGJs